Application of Business Judgement Rule Doctrine in Case Settlement (Case Study of Corruption Crime of PT Asuransi Jiwasraya (Persero)) - Josef Martua Prasetyo Manik (Jurnal Indonesia Sosial Teknologi, 2024)
As is known in Corporate Law, corporate law experts divide 2 (two) major groups of business entity forms, one of which is a legal entity. Included in this group is the Limited Liability Company (PT) The thing that distinguishes between the two types of business entities incorporated and unincorporated lies in the responsibility of the company owner. In relation to practice, business people are more interested in establishing a business entity in the form of a legal entity, namely a Limited Liability Company ("PT"). The reasons why business people are more likely to choose a PT, namely the continuity of a business entity in the form of a PT does not depend on the personalities of the owners but on the capital accumulated, the separation of responsibilities between the company owner and the company, and because PT can be used as a means to move towards a more liberal and open business. In carrying out the management of a PT, the Board of Directors performs its duties with reference to the principle of good faith. In this case, it is actually difficult to distinguish which actions are actually carried out in good faith and which actions are reasonable in carrying out their duties. In relation to its duties and authorities, the management of the Company carried out by the Board of Directors includes running business activities, controlling, and making business decisions that have an impact on the Company, even though these decisions can cause profits or losses.